Sport Tourism Strategy to Increase Indonesian Tourism: Case Study of Increasing Tourists During the Byon Combat Showbi 4 Event - Ainil Mardiah; I Made Sucipta Adnyana; Nyoman Gede Mas Wiartha; A.A. Istri M. Septiviari; Dewa Gde Ngurah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research is a qualitative research with a descriptive approach. Qualitative research with a descriptive approach has the main objective of analyzing and describing each main topic used in this study, namely Sport Tourism, Tourism, Byon Combat Showbis 4 Indonesia versus Malaysia. The data used in this study are secondary data that researchers obtain from each source that is most often used in qualitative research including scientific articles, books, magazines, and credible websites. The sources mentioned above are analyzed with the stages of data collection, data reduction, data selection, and drawing conclusions. The result in this article show that Byon Combat is currently the combat sport event with the largest exposure in Indonesia. In Byon Combat Showbiz 3, Byon broke the record of more than three hundred thousand pay per view sales, the most in Indonesia and even in Asia and had more than 23 million viewers on YouTube. In Byon Combat Showbiz 4, Byon had a slightly larger number of pay per views than Byon Combat Showbiz 3, namely more than 400 thousand Pay Per Views and more than 24 million viewers on YouTube. In addition, the variety of Byon Combat Showbiz 4 viewers is more diverse than Byon Combat Showbiz 3 because it pits Indonesian vs. Malaysian fighters. Through this platform, many Asian people, especially Indonesia and Malaysia, know more about Indonesia and some viewers also go directly to Indonesia. This can indirectly increase tourism in Indonesia. Moreover, if Byon Combat continues.